A cyclist, a family or a vehicle? Claiming the road with the e-cargo bike - Caulfield, Brian; Egan, Robert (My University, 2026)
The ability to cycle on roads shared with motor traffic – or “vehicular cycling” – is a basic competence in countries with low rates of cycling. Through electric pedal assistance, e-bikes can reduce the physical demands of vehicular cycling. With their larger size and capacity to carry multiple children, e-cargo bikes may likewise change how vehicular cycling is experienced and practiced. In this paper, we present an analysis of vehicular cycling in Ireland with the e-cargo bike, focusing on the interview accounts of participants based in four major Irish cities: Dublin, Belfast, Galway, and Cork. We found that most participants felt more respected by motorists, more secure, more powerful, and more entitled as road users when e-cargo cycling. The materials of the e-cargo bike on the road appeared to subvert the established meanings of the bicycle and the cyclist, challenging the hegemony of the private car as the dominant “vehicle” of public space and as the quintessential “family” transport mode. Our unique analysis of e-cargo vélomobility in the spaces of automobility shows how the materiality of the e-cargo bike on the road can help to question dominant meanings of cycling in a car-centric society.
PUBLISHED
Keywords: e-cargo bike; e-bike; vélomobility; risk; practice theory; automobility; Smart & Sustainable Planet; Environmental aspects of transportation; Transport